Analysis of the Effect of Self-Efficiency and Self-Motivation on Business Success (Case Study on Entrepreneurs Food at Cemara Asri Medan) - Mario Andriaskiton; Fitri Natalia (Enrichment : Journal of Management, 2022)
The purpose of the study was to determine the effect of self-efficacy on the business success of the Cemara Asri Medan food entrepreneur, to determine the effect of self-motivation on the business success of the Cemara Asri Medan food entrepreneur, and to determine the effect of self-efficacy and self-motivation on the success of the Cemara complex food entrepreneur business. Asri Medan. The research method uses descriptive quantitative. Methods of data collection using a questionnaire that will be measured using a Likert scale. The data analysis technique used is multiple linear regression analysis, partial testing, simultaneous testing and testing the coefficient of determination. The results of this study indicate that partially or simultaneously the variables of self-efficacy and self-motivation have a significant influence on business success at the food entrepreneur of the Cemara Asri Medan complex.